The effect of using physical skill exercises for devl0ping power speed for passing in soccer - naje, deaa; kadem, amad; saleam, ismaeal (Journal of Physical Education, 2010)
The that represent power speed the skill full aspect represent s motor pee e study c0ntains the importance of physical aspect d for aim of stdy is to know effect of skill exercises in develpping. Experimental group the 17-19 years the players are divided in to gro